US Foreign Policy Towards Palestinian - Israel Conflict From 2001 to 2018 - Guesseir, Bahi, Radja Hana (جامعة الوادي University of Eloued, 2019)
Since the beginning of the Palestinian-“Israeli” conflict in the mid 20th century, the strategies of U.S. foreign policy towards the conflict varied from one period to another and from one president to another. This study attempts to clarify the factors that made U.S foreign policy and casts light on the most important conflict spots. Also it aims at investigating the political strategies and practices of the Bush, Obama and Trump's administration, from 2001 to 2018 and their impact on the conflict. The method adopted to achieve this purpose is a descriptive-analytical method, where the study intends to describe the historical events of the Palestinian-“Israeli” conflict and to analyze the impact of the political strategies and practices adopted by the three administrations. The results obtained from the study demonstrate that the U.S. foreign policy political strategies and practices of three administration are completely biased to “Israel” and all the initiatives put forward by them do not give the Palestinian people the most basic rights to self-determination and the establishment of an independent state.منذ بداية الاستعمار في منتصف القرن العشرين , اختلفت إستراتيجيات السياسة الخارجية الأمريكية تجاه الصراع الفلسطيني الإسرائيلي من فترة إلى أخرى ومن رئيس إلى آخر. هذه الدراسة حاولت توضيح العوامل المساهمة في صنع السياسة الخارجية الامريكية كما ركزت على اهم محطات الصراع . ومن أهم أهداف هذه الدراسة هو دراسة الاستراتيجيات والممارسات السياسية للإدارات الثلاثة ومدى تأثيرها على الصراع . وللوصول إلى أهداف الدراسة استعملنا المنهج الوصفي التحليلي لوصف الاحداث التاريخية وتحليل الاستراتجيات المتبعة من قبل الادارات وتأثيرها . ومن النتائج التي توصلت إليها الدراسة ان الاستراتجيات والممارسات السياسية للإدارات الثلاثة تتمثل في الانحياز الكامل لإسرائيل كما ان كل المبادرات التي طرحت من قبلهم لا تعطي الشعب الفلسطيني أبسط حقوقه في تقرير مصيره وإقامة دولته المستقلة.
Keywords: Political Practices, Political Strategies, The Palestinian-Israeli Conflict, Three administrations ,U.S. Foreign Policy.; لاستراتجيات والممارسات السياسية , الصراع الفلسطيني الإسرائيلي , الإدارات الثلاثة , السياسة الخارجية الامريكية